Ibn Sina’s Thought as a Foundational Solution to Contemporary Issues in Islamic Education and Neuroscience - Raghda Mahmoud (Walidem Institute and Publishing (WIP), 2025)
Objective: The rapid advancement of technology, social transformation, and the growing influence of neuroscience have generated new challenges and opportunities in the field of Islamic education. Contemporary neuroscience provides scientific insights into brain mechanisms, cognition, memory, emotion, and behavior, while Islamic intellectual tradition has long addressed similar concerns through philosophical and theological reflections on reason and learning. This study aims to analyze contemporary issues emerging at the intersection of Islamic education and neuroscience by examining Ibn Sina’s intellectual legacy and assessing the potential for integrating classical Islamic thought with modern neuroscientific findings in educational practice. Theoretical framework: The theoretical framework of this study is grounded in Ibn Sina’s epistemology of the intellect and rational soul, combined with contemporary neuroeducation theories that explore learning processes through brain-based research. Literature review: The literature review highlights prior studies on Islamic educational philosophy, Ibn Sina’s cognitive theory, and recent neuroscience research, while also identifying unresolved challenges such as neuromyths, limited neuroscience literacy among educators, biological reductionism, and ethical concerns related to neurotechnology. Method: This research employs a descriptive qualitative method based on library research. Primary sources include the Qur’an and classical Islamic educational texts, particularly Ibn Sina’s works, while secondary sources consist of contemporary neuroscience and educational research. Data are analyzed thematically to identify points of convergence and tension between Islamic educational values and neuroscientific perspectives. Results: The findings indicate that neuroscience can significantly enhance the effectiveness of Islamic education when applied critically and ethically. However, integration must avoid reductionist interpretations that neglect spiritual, moral, and metaphysical dimensions. Ibn Sina’s concept of the intellect and rational soul provides a valuable philosophical bridge that supports a holistic understanding of human learning. Implications: The implications of this study suggest the need for an integrative educational model that balances scientific innovation with Islamic values, fostering ethical awareness and humanistic learning. Novelty: The novelty of this research lies in its interdisciplinary synthesis of Ibn Sina’s cognitive philosophy with contemporary neuroscience to address current educational challenges in the era of digitalization and neurotechnology.